On the metrization - Azram, Mohammad (University of Alba Iulia, Romania, 2011)
In this article, we have studied the concept, property and interrelationship of being T1-space, discrete space, metrizable space, separable space and topologically totally bounded space with finite, infinite and countable underlying set. With some additional conditions we have established equivalence between T1-space, discrete space, metrizable space, separable space and topologically totally bounded space. At the end we have extended the same to a disjoint (free) union.